Application and research on Regenerative High Temperature Air Combustion technology on low-rank coal pyrolysis. (15th October 2015) - Pei, Pei; Wang, Qicheng; Wu, Daohong
Highlights: Based on RHTAC technology, RRTC has been developed, and was adopted by Shenwu Pyrolysis Process (SPP). For RRTC, the low calorific value gas fuel can be used and the heat loss in fume exhausted is low. The RRTCs can realize accurate temperature control and the separation of volatile materials and fume in the pyrolyzer. Tar yield and gas quality is improved. Moreover, SPP could solve some technical problems for low-rank coal pyrolysis. Abstract: Regenerative High Temperature Air Combustion (RHTAC) technology is composed of circular-ceramic regenerator, burners, small four-way reversing valve and control system. RHTAC technology works by using the regenerator in burners to complete heat exchange between the high-temperature fume exhausted and the combustion air. Based on RHTAC technology, Regenerative Radiant Tube Combustor (RRTC) has been developed, and was adopted by Shenwu Pyrolysis Process (SPP), which is a new pyrolysis technology with the heat-carrier-free rotating bed. SPP was researched and developed to upgrade low-rank coal into the upgraded coal, tar and pyrolyzing gas. Presently, various coals from China and other countries have been conducted, including Lignite and Long flame coal. To understand the function of the RRTCs in SPP, a pilot plant has been constructed and used to investigate the effects of the RRTCs on the fume and pyrolyzer temperature distributions and pyrolyzing products. The results show that low calorific value gas fuel (>700 kcal/Nm 3 ) can be used, the heat loss in fume exhausted is low (temp. about 150 °C), so thermal efficiency of the RRTC is greatly improved; the RRTCs can realize accurate temperature control and the separation of volatile materials and fume in the pyrolyzer, so as to increase tar yield and improve gas quality. The tar yield is more than 90% of the Gray-King tar yield; the pyrolyzing gas contains high contents of CH4, H2 and CO. Moreover, SPP could solve some technical problems, such as high dust content in coal tar, likely blockage of pipeline and greatly increasing the subsequent tar processing cost.